Penerapan VIKOR Dalam Pemilihan Calon Ketua DPC Peradi Vikor - Atika Suri; Nelly Astuti Hasibuan; Fadlina Fadlina (Journal of Computer System and Informatics (JoSYC), 2021)
The Indonesian Advocates Association (PERADI) is an advocate organization referred to in law number 18 of 2003 ("Law No.18 / 2003") on advocates namely that PERADI is the only forum for a free and independent advocate profession formed in accordance with the provisions of the law this invite. In the election of PERPC Medan DPC chairman, it was still done manually by means of the selection process first. Therefore a decision support system is designed so that the selection is more effective and accurate. Decision Support System is made by applying the VIKOR method. The system created will provide recommendations for the selection of candidates for the PERADI DPC Chair in Medan by involving five criteria, namely discipline, commitment, leadership, broad-minded and ethical with five alternatives. By using Microsoft Visual Studio 2008 for the design of decision support systems and Microsoft Access 2016 as a database. This research can provide convenience to PERADI Medan in making decisions on the selection of candidates for the PERADI DPC chairman in Medan and provides objective and accurate results in the decision to elect the candidates for PERADI DPC Chair in Medan.